2017
DOI: 10.1016/j.mayocp.2017.08.021
|View full text |Cite|
|
Sign up to set email alerts
|

The Association of Serum Free Light Chains With Mortality and Progression to End-Stage Renal Disease in Chronic Kidney Disease: Systematic Review and Individual Patient Data Meta-analysis

Abstract: Financial support and conflict of interest disclosureAB is an employee of Binding Site and PC has received research funding from Binding Site.The results presented in this paper have not been published previously in whole or part, except in abstract format. Patients and MethodsOn December 28, 2016, we searched four databases (MEDLINE, Embase, CINAHL, PubMed) and conference proceedings, for studies presenting independent analysis of associations between sFLC and mortality or progression to end-stage renal dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Elevated serum free k light chains and free l light chains levels appeared to be associated with mortality; however, the association disappeared after adjustment for a propensity score including age, CKD stage, and aortic calcification. Furthermore, one meta-analysis pooling data from five prospective cohort studies showed that serum free k and l light chains levels were independently associated with mortality (33). The serum free k and l light chains values above the upper limit of normal (43.3 mg/L) were independently associated with mortality (hazard ratio, 1.45; 95% confidence interval, 1.14 to 1.85).…”
Section: Discussionmentioning
confidence: 99%
“…Elevated serum free k light chains and free l light chains levels appeared to be associated with mortality; however, the association disappeared after adjustment for a propensity score including age, CKD stage, and aortic calcification. Furthermore, one meta-analysis pooling data from five prospective cohort studies showed that serum free k and l light chains levels were independently associated with mortality (33). The serum free k and l light chains values above the upper limit of normal (43.3 mg/L) were independently associated with mortality (hazard ratio, 1.45; 95% confidence interval, 1.14 to 1.85).…”
Section: Discussionmentioning
confidence: 99%
“…Middle molecules have a broad range of molecular size from 500 to 60 kDa and include a number of cytokines, adipokines, growth factors, and other signalling proteins that are significantly elevated in dialysis patients compared with those in individuals with normal kidney function. The serum levels of interleukin (IL) 1β (17.5 kDa), IL-6 (21.0–28.0 kDa), and IL-18 (18.0 kDa) as well as κ (22.5 kDa) and λ (45.0 kDa) free light chains (FLCs) are also elevated in patients with advanced chronic kidney disease (CKD) [2]. The levels of fibroblast growth factor (FGF)-23 (22.5–32.0 kDa), a growth factor involved in renal phosphate handling and the development of mineral and bone disorders in CKD, also can increase up to > 200-fold.…”
Section: Introductionmentioning
confidence: 99%
“…Like other uremic toxins, λFLC (and κFLC) determined with the Freelite polyclonal antibody assay accumulate progressively with declining renal function, reaching highest serum concentrations in end-stage kidney disease [23]. Polyclonal FLC levels can be regarded as interesting biomarkers because they are associated with patient outcome, independently predicting mortality and further decline of renal function in chronic kidney disease patients [24][25][26][27]. Using the Freelite assay to measure FLC, Hutchison et al were the first to demonstrate a significant increase of the κ/λ-FLC ratio in patients with chronic kidney disease compared to healthy controls.…”
Section: Discussionmentioning
confidence: 99%